2022
DOI: 10.1177/21501319221110421
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Postnatal Depression During COVID-19 Pandemic: The Role of Health Care Providers

Abstract: Background: The fast spread of COVID-19 can cause some psychological disorders for men. One of the psychological disorders is paternal postpartum depression (PPD). The aim of the present research was to review studies that have investigated paternal postpartum depression during the COVID-19 pandemic. Materials and Methods: For this narrative review, databases such as Google Scholar, Scientific Information Databases (SID), Magiran, PubMed, Web of Science, and Scopus were searched for the full texts of published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
0
12
0
2
Order By: Relevance
“…Segre et al (2010) found that patients interviewed about PPD screening felt it acceptable for nurses to lead mental health screening and counseling practices. Nurses, in both inpatient and ambulatory settings, are critical liaisons for matching patients and family members with proper referrals and available resources (Yazdanpanahi et al, 2022). Nurses are adept at identifying early concerns and promoting information and education that could prepare families for potentially challenging emotions during pregnancy and postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Segre et al (2010) found that patients interviewed about PPD screening felt it acceptable for nurses to lead mental health screening and counseling practices. Nurses, in both inpatient and ambulatory settings, are critical liaisons for matching patients and family members with proper referrals and available resources (Yazdanpanahi et al, 2022). Nurses are adept at identifying early concerns and promoting information and education that could prepare families for potentially challenging emotions during pregnancy and postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Lockdowns and teleworking caused family–work conflict and led to lower work satisfaction and efficiency for women than men [ 59 ]. Furthermore, under the ongoing COVID-19 pandemic, women seem to be more worried about their loved ones and the family, which may interfere in their perceived family functioning, while men are more occupied with effects on economic issues [ 60 ] In connection to this, the correlation between paternal COVID-19-related concerns about employmentand postpartum depression may be explained by the association between unstable employment status and postnatal depression in fathers [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Die Forschergruppe betont, dass die durch diese Pandemie verursachten psychischen Störungen das Auftreten für väterliche postpartale Depressionen verstärken kann. Was wiederum zur Folge hat, dass Väter mit schlechter mentaler und psychischer Gesundheit ihren Frauen und Kinder keine umfassende Unterstützung zukommen lassen können 20 .…”
Section: Diskussionunclassified
“…Je nach Studienlage leiden pränatal zwischen 4,1 % und 16,0 % und postnatal zwischen 2,4 und 18,0 % der Väter an einer Angststörung [19]. Kommen Was wiederum zur Folge hat, dass Väter mit schlechter mentaler und psychischer Gesundheit ihren Frauen und Kinder keine umfassende Unterstützung zukommen lassen können [20].…”
Section: Diskussionunclassified